Urban Environment: risk, vulnerability and cognition from the experience of users of green areas of public Aracaju (SE) - Gois, Douglas Vieira; Luiz Guimarães de Figueiredo, Miguel; Melo e Souza, Rosemeri (Geografares, 2014)
The light of the theory of risk and environmental vulnerability, this study aims to conduct an analysis of the users’ perception of public green areas Aracaju on the consequences arising from the uneven distribution of urban trees in this city. We sought to address the cognition of the population as a key factor for legitimacy, or not, the government practices regarding policies of afforestation in urban Aracaju. Furthermore, we emphasize the cognitive act as a fundamental process for the decision facing the risks and vulnerabilities associated with the urban environment.